Falls amongst older people in Southeast Asia: a scoping review. (April 2017) - Romli, M.H.; Tan, M.P.; Mackenzie, L.; Lovarini, M.; Suttanon, P.; Clemson, L.
Abstract: Objectives: The older population in the Southeast Asian region is accelerating and is expected to surpass the proportion of the ageing population in North America and Europe in the future. This study aims to identify the research literature related to falls among older people in Southeast Asia, to examine current practice and discuss the future direction on falls prevention and interventions in the region. Study Design: A scoping review design was used. Methods: A systematic literature search was conducted using the Medline, CINAHL, AMED, Ageline, PsycINFO, Web of Sciences, Scopus, Thai-Journal Citation Index, MyCite and trial registries databases. Results: Thirty-seven studies and six study protocols were included, from Thailand, Malaysia, Singapore, Vietnam, Indonesia and the Philippines. One-sixth of the studies involved interventions, while the remainder were observational studies. The observational studies mainly determined the falls risk factors. The intervention studies comprised multifactorial interventions and single interventions such as exercises, educational materials and visual correction. Many of the studies replicated international studies and may not have taken into account features unique to Southeast Asia. Conclusion: Our review has revealed studies evaluating falls and management of falls in the Southeast Asian context. More research is required from all Southeast Asian countries to prepare for the future challenges of managing falls as the population ages. Highlights: The falls scenario among community-dwelling older people in Southeast Asia was slightly different than the Western studies. The investigation on falls in Southeast Asia is in infancy while many replicating other international studies. Limited number of intervention studies was conducted in Southeast Asia. Intervention for falls in Southeast Asia might require different approach suitable with the local and cultural context. More feasibility and joint studies among the ASEAN countries are warranted due to limited economic capacity and expertise.